TAFSIR AL-QURAN PERTAMA DI KALIMANTAN BARAT - Jabbar, Luqman Abdul (Khatulistiwa, 2015)
Ancient manuscript of the Tafsir Surat Tujuh (interpretation of surah seven) by Muhammad Imran Basiuni is a reflection the methodological of the study of the Qur’an in the early 20th century in the kingdom of Sambas, West Kalimantan. And it is the only masterpiece of interpretation that was, and has been written by the scholar in West Kalimantan at the time. The ancient manuscript of Tafsir Surat Tujuh is purely his own hand-written work, and does not have a duplicate, and has published in the Kingdom of Sambas since the beginning of the 20th century, which is still intact and kept in the Sambas Museum of Islamic Civilization. The manuscript thematically contains theology and righteous deeds. Meanwhile,the methodological pattern of this manuscript seemsto be more free and not bound to the classic methodology, if any,the coherence was the only method he used. In addition the ijmali method was also in use, which can be seen in the lexical-linguistic analysis of the manuscript as commonly found in books of classical interpretation with their interpretational language.